Tramas narrativas de la enseñanza de la matemática y mejoramiento de la raza en la sociedad colombiana - Guerrero-Recalde, Néstor Fernando (Revista Científica, 2016)
This article seeks to show the reasons which have led to consider the school as a privileged institution for the civilizing process. In particular understand the reasons which have led to argue that mathematical knowledge are key to the formation of the civilized individual parts. To account for this thesis was chosen in the history of Colombia the period 1873-1960, which have called period of "eugenic math" or "period of improving the race." In this period we are oriented to eliminate those features of our society seen as savage and barbaric speech. Also, this speech was accompanied with the idea of building a new republic from scientific educational devices. The most prominent figure in this period were the german physical and mathematical Julius Sieber.